الفضاءات المكانية: التشكل والتمظهر مقاربة نقدية في رواية ملكة العنب لـ " نجيب الكيلاني - نصير, فاطمة (Revues faculté des lettres et des langues; No 17 (2015): مجلة كلية الآداب واللغات)
المكان من البنيات الأساسية المشكلة لنص سردي متكامل ، يساهم في تفعيل دور القارئ / المتلقي ، من خلال إيهامه بواقعية الأحداث عن طريق تصويرها في أمكنة متعددة تتفاوت من حيث جمالياتها ومن حيث طبيعة تشكلها داخل المحكي القصصي . في هذا سيتم مقاربة المكان في رواية " ملكة العنب " للدكتور " نجيب الكيلاني " ، ووصف الأمكنة ، والحكم على مدى نجاح السارد في تقديم المكان كبنية ضرورية داخل نسيج النصوص السردية . Space is one of the essential  sructures that form the a entire narrative text. it contributes in  the role of reader through by deluding him about the realistic aspects of events by photographing them in different spaces which varies in their  esthetic  aspect and their  nature  inside the spoken narrative. This article I deals with   the space in the novel of Najeeb El Kilani entitled ; The Queen of grapes « Malikat el Ineb »  and to finally arrive to judge  if the writer succeeded in  presenting  spaces as important structures inside the texture of the narrative texts